(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
Conventional spray pyrolysis technique was employed for the preparation of cadmium sulphide (CdS) thin films that deposited onto glass substrates at 573 K from cadmium acetate and thiourea precursor solution for different deposition time. The surface morphology, compositional study and optical properties of the films have been characterized by Scanning Electron Microscopy (SEM) attached with an EDX and UV spectroscopy, respectively. The SEM micrographs of deposited film showed uniform deposition over the substrate. The EDX spectra of CdS thin films revealed that films are stoichiometric. All the films demonstrated more than 70% transmittance at wavelengths longer than 600 nm. The optical absorption coefficient (?) of the CdS films was determined from transmittance spectra. For different thickness (110 - 250nm) of the films, the direct band gap was found in the range of 2.15 2.48 eV. Resistivity (?) of CdS thin films was measured in the temperature range of 300 to 550 K. Activation energy (?E) was found in the range from 0.047 to 0.078 eV. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15678 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 33-41, 2013